ANALISIS DETERMINAN ISLAMICITY PERFORMANCE INDEX PADA BANK UMUM SYARIAH DI INDONESIA - Kristianingsih Kristianingsih; Mahesa Dava Wardhana; Setiawan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Islamicity Performance Index (IPI) is a model developed to measure the performance of Islamic banks with a socio-economic approach. This study reveals the factors that affect the Islamicity Performance Index (IPI) which is represented by the Profit Sharing Financing Ratio (PSR) index. With a sample of 12 Islamic Commercial Banks (BUS) in Indonesia, this study uses static and dynamic panel data analysis. The data used is secondary data derived from the annual financial statements of each BUS. The results showed a significant positive effect of TPF and FDR on PSR in the static and dynamic models, significant negative NPF on PSR in the static model, significant positive NPF on PSR in the dynamic model, insignificant negative BOPO on PSR in the static model, positive insignificant BOPO on PSR in the dynamic model, significant positive PSR (-1) on PSR in the dynamic model. Simultaneously the independent variable is able to explain the dependent variable by 95.8%.